Tryptophan, kynurenine, and kynurenine metabolites: Relationship to lifetime aggression and inflammatory markers in human subjects. (September 2016) - Coccaro, Emil F.; Lee, Royce; Fanning, Jennifer R.; Fuchs, Dietmar; Goiny, Michel; Erhardt, Sophie; Christensen, Kyle; Brundin, Lena; Coussons-Read, Mary
Highlights: Impulsive aggressive individuals have been reported as having elevated plasma levels of inflammatory markers, compared with healthy and psychiatric controls. However, in the setting of chronic inflammation, aggression may be due to changes in plasma tryptophan, kynurenine, and their metabolites. Thus, we assessed plasma levels of these substances in these types of subjects and found that plasma tryptophan levels were no different in aggressive subjects compared with healthy controls, though plasma kynurenine levels were significantly lower in aggressive subjects compared with healthy controls. These findings are in contrast to what has been reported in other behavioral disorders such as depression and suggest that alterations of the tryptophan-kynurenine pathway may be quite different in aggressive compared to depressed patients. Abstract: Inflammatory proteins are thought to be causally involved in the generation of aggression, possibly due to direct effects of cytokines in the central nervous system and/or by generation of inflammatory metabolites along the tryptophan-kynurenine (TRP/KYN) pathway, including KYN and its active metabolites kynurenic acid (KA), quinolinic acid (QA), and picolinic acid (PA). We examined plasma levels of TRP, KYN, KA, QA, and PA in 172 medication-free, medically healthy, human subjects to determine if plasma levels of these substances are altered as a function of trait aggression, and if they correlate with current plasma levels of inflammatory markers. Plasma levels of C-reactive protein (CRP), interleukin-6 (IL-6), and soluble interleukin-1 receptor-II (sIL-1RII) protein were also available in these subjects. We found normal levels of TRP but reduced plasma levels of KYN (by 48%), QA (by 6%), and a QA/KA (by 5%) ratio in subjects with Intermittent Explosive Disorder (IED) compared to healthy controls and psychiatric controls. Moreover, the metabolites were not associated with any of the inflammatory markers studied. These data do not support the hypothesis that elevated levels of KYN metabolites would be present in plasma of subjects with IED, and associated with plasma inflammation. However, our data do point to a dysregulation of the KYN pathway metabolites in these subjects. Further work will be necessary to replicate these findings and to understand their role in inflammation and aggression in these subjects.